The Use of Video-Based Learning Platforms for Teacher Training: An Analysis of Content Engagement and Instructional Effectiveness of YouTube Channels - Hartono; Ratnaningsih (CV. Simpati Cloud, 2025)
This study aims to analyze content engagement and instructional effectiveness of YouTube channels utilized as platforms for teacher training. Employing a descriptive qualitative approach supported by quantitative data, the study evaluated 30 videos from 10 popular educational channels using content analysis and user engagement metrics. The findings reveal that videos lasting 5–10 minutes with a systematic narrative structure, illustrative visuals, interactive delivery, and the visual-auditory presence of instructors demonstrate the highest levels of instructional effectiveness and viewer retention. The average video completion rate reached 68%, and positive comments accounted for up to 82% of user feedback. In contrast, longer videos delivered in a monologic style tended to generate lower levels of engagement. These findings underscore the importance of instructional design in producing effective video-based teacher training content. The study recommends enhanced content curation and targeted training in educational video production for teachers and educational institutions to optimize YouTube’s potential as a platform for ongoing professional development.